2020
DOI: 10.1002/lary.28757
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Aspiration Pneumonitis Caused by Spontaneous Cerebrospinal Fluid Fistulae of the Skull Base

Abstract: Objectives/Hypothesis Spontaneous cerebrospinal fluid (CSF) leaks of the skull base are associated with obesity, multiparity, and elevated intracranial pressure. Although spontaneous CSF leaks often present with rhinorrhea, they can be an underdiagnosed cause of chronic aspiration pneumonitis, a complication that has not been previously reported in detail. Study Design Retrospective case series. Methods The authors retrospectively reviewed all patients undergoing surgical repair of CSF fistulae at the Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 19 publications
0
16
0
2
Order By: Relevance
“…Lung lesions are considered to be secondary to the chronic aspiration of leaked CSF (6). Supporting this view, a chest CT scan shows airway-centered ground glass opacities with or without bronchial wall thickening and a tendency of lower lobe predominance (2,5,6). In our patients, the upper lung zone was also involved.…”
Section: Discussionmentioning
confidence: 78%
“…Lung lesions are considered to be secondary to the chronic aspiration of leaked CSF (6). Supporting this view, a chest CT scan shows airway-centered ground glass opacities with or without bronchial wall thickening and a tendency of lower lobe predominance (2,5,6). In our patients, the upper lung zone was also involved.…”
Section: Discussionmentioning
confidence: 78%
“…Zada et al first reported a case about chronic aspiration-induced pneumonitis caused by spontaneous ethmoid sinus meningocele with CSF rhinorrhea, and indicated that increased diagnostic complexity associated with pulmonary complications led to unnecessary intervention and treatment delays [ 7 ]. CSF rhinorrhea can be considered as a cause of chronic pneumonitis despite the lack of direct evidence [ 8 ]. A controlled clinical trial has shown that sinonasal secretions can be transferred to the lungs whether in patients with cystic fibrosis or healthy subjects [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the chest CT showed imaging findings similar to those of aspiration pneumonia in bedridden patients who are always in a supine position. It was recently reported that spontaneous CSF leaks can cause chronic aspiration pneumonitis [ 4 , 5 ]. The pathology in this case may have had the same mechanism.…”
Section: Discussionmentioning
confidence: 99%